2022
DOI: 10.1021/acsanm.2c02750
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Surface-Enhanced Raman Scattering Detection of a SARS-CoV-2 Biomarker Using Flexible and Transparent Polydimethylsiloxane Films with Embedded Au Nanoplates

Abstract: Coronavirus disease 2019 (COVID-19) remains an ongoing issue worldwide and continues to disrupt daily life. Transmission of infection primarily occurs through secretions when in contact with infected individuals, but more recent evidence has shown that fomites are also a source of virus transmission, especially in cold-chain logistics. Traditional nucleic acid testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contamination in cold-chain logistics is time-consuming and inaccurate because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 50 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…45 Notably, the LOD of this assay was considerably superior to that of the commonly used polymerase chain reaction-based technique and some other previously reported label-free SERS-based detection methods. [46][47][48] Even though the LOD of our method cannot compare with that of some labeled SERS methods and some other optical, electrochemical, and field-effect transistor sensors, [49][50][51][52][53] our assay takes ∼30 min to complete without any sample pretreatment. Thus, our work stands out for its rapid detection speed, noninvasiveness, and nonautofluorescence interference and provides a solid platform for protein testing.…”
Section: Sers Detection Of S and N Proteinsmentioning
confidence: 99%
“…45 Notably, the LOD of this assay was considerably superior to that of the commonly used polymerase chain reaction-based technique and some other previously reported label-free SERS-based detection methods. [46][47][48] Even though the LOD of our method cannot compare with that of some labeled SERS methods and some other optical, electrochemical, and field-effect transistor sensors, [49][50][51][52][53] our assay takes ∼30 min to complete without any sample pretreatment. Thus, our work stands out for its rapid detection speed, noninvasiveness, and nonautofluorescence interference and provides a solid platform for protein testing.…”
Section: Sers Detection Of S and N Proteinsmentioning
confidence: 99%
“…On the other hand, the surface-enhanced Raman scattering (SERS) technique has been extensively adopted for virus detection, owing to its ultrahigh sensitivity and label-free detection. As a potent analytical technique for diagnostic investigations, many researchers have adopted SERS for the detection of various viruses such as SARS-CoV-2 [ 30 ], influenza viruses A and B [ 31 ], rotavirus [ 32 ], and hepatitis C virus [ 33 ]. Therefore, several studies have suggested that combining SERS with LFA can improve assay sensitivity.…”
Section: Virus Detection On Microfluidic Platformmentioning
confidence: 99%
“…This technique has the advantage to be used non-invasively, label-free and can enable a fast analysis. Experiments with SERS already revealed that an analysis and detection of the SARS-CoV-2 virus and other variants is possible [8][9][15][16][17][18].…”
Section: Invited Papermentioning
confidence: 99%